Studies on antioxidant activity of red, white, and black pomegranate (Punica granatum L.) peel extract using DPPH radical scavenging method - Uswatun Chasanah (Universitas Muhammadiyah Malang, 2020)
Pomegranate (Punica granatum L.) has high antioxidant activity. In Indonesia, there are red pomegranate, white pomegranate, and black pomegranate. The purpose of this study was to determine the antioxidant activity of red pomegranate peel extract, white pomegranate peel extract, and black pomegranate peel extract. The extracts prepared by ultrasonic maceration in 96% ethanol, then evaporated until thick extract was obtained and its antioxidant activity was determined using the DPPH radical scavenging method. This study showed that all pomegranate peel extract varieties have potent antioxidant activity and the black pomegranate peel extract has the highest antioxidant power.